2016
DOI: 10.1370/afm.1976
|View full text |Cite
|
Sign up to set email alerts
|

Overstimulated Consumers or Next-Generation Learners? Parent Tensions About Child Mobile Technology Use

Abstract: PURPOSE Mobile technology is ubiquitous, but its impact on family life has not been thoroughly addressed in the scientific literature or in clinical practice guidelines. We aimed to understand parents' views regarding mobile technology use by young children, aged 0 to 8 years, including perceived benefits, concerns, and effects on family interactions, with the goal of informing pediatric guidelines. METHODSWe conducted 35 in-depth, semistructured group and individual interviews with English-speaking caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 13 publications
12
98
0
Order By: Relevance
“…16 In reality, parents can be reassured that their children will learn to use digital media quickly when they are introduced at home or in school.…”
Section: How Have Mobile and Social Media Changed The Ability Of Advementioning
confidence: 99%
See 1 more Smart Citation
“…16 In reality, parents can be reassured that their children will learn to use digital media quickly when they are introduced at home or in school.…”
Section: How Have Mobile and Social Media Changed The Ability Of Advementioning
confidence: 99%
“…Today, more children own and use mobile devices independently, 13 making monitoring and regulation much more difficult. 16,68 More research is needed on how parents can best supervise and guide their children's media use.…”
Section: Health and Developmental Risks Of Media Use What Are The Devmentioning
confidence: 99%
“…Beyond the incorporation of mobile devices into family routines, another clear content area that emerged was the use of mobile devices for behavior management, reflecting findings from several other studies [17,18,24,25]. found that parents commonly used media "to keep their kids occupied while they [parents] get chores done."…”
Section: Mobile Device Use Content and Contextmentioning
confidence: 71%
“…[11] Other studies have reported similar tensions around parental beliefs related to mobile devices with many parents simultaneously recognizing the potential benefits of mobile devices (such as children's learning or entertainment) and expressing concerns about potential drawbacks to mobile device use (such as exposure to inappropriate content or lack of engagement with others). [17][18][19] However, beyond these overarching views of mobile devices, the specific role of mobile devices in the daily lives of families as well as the acceptability of using mobile devices for intervention delivery in low resource populations remains unknown. Therefore, prior to moving forward with an intervention, formative research to understand the feasibility of mobile devices as a mode of intervention delivery in rural, low resource audiences is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue we also call for diverse readers to help foment a revolution by sharing on-the-ground innovations in primary health care. 1 The degree to which mobile technology use by young children affects families is evaluated in an in-depth qualitative study by Radesky et al 2 In a complement to a recent Annals supplement on peer support for diabetes self-management, 3 a metaanalysis of peer support intervention trials among adults with diabetes discovers a small but significant effect on glycosylated hemoglobin, and larger effects among studies with predominantly Hispanic participants and among predominantly minority participants. 4 If this personal intervention has an effect on this impersonal outcome, it would be interesting to know the effect of peer support on more overtly patient-and community-centered outcomes.…”
mentioning
confidence: 99%